Attitudes of students of the Department of Special Education towards their professional future (Journal of the College of Basic Education, 2023)
Psychologists agree that attitudes are an important part of our lives, and play a major role in directing and determining the individual's behavior in many life situations, and at the same time they provide us with true predictions about the individual's behavior in those situations, and trends also help in determining the groups with which the individual is associated and professions. Which he chooses, and it has a great influence on our judgments and our perception of others, in addition to its role in directing the individual’s responses in an almost constant manner towards things and topics in the environment (Wahid, 2001, p. 42).Trends play an important role in achieving the social harmony of the individual through the individual's acceptance of the trends embraced by the group, and he shares them with them. The trends also give the individual's daily life meaning, significance, and significance, as his behavior agrees with his trends.Motives are linked to trends, and trends provoke motives, which in turn are the engines of behavior that activate it and direct it towards a specific goal, which is satisfying the need, that is, the individual's tendency towards a specific thing becomes a willingness to work, perceive, think, and feel towards the elements of the environment.In the light of these data, it can be said that the performance of the individual and the level of his achievement of the work that he practices and his adaptation to the conditions of that work may be affected by the type of attitudes that he carries towards the work that he practices, and that the chances of success and development in the work may also be affected by these trends. The Department of Special Education may bear negative attitudes towards their professional future, which is reflected negatively on their motivation, level of performance, achievement, and adaptation to future working conditions. You may be affected by the kind of trends he carries towards his future career.